2020
DOI: 10.1111/1750-3841.15142
|View full text |Cite
|
Sign up to set email alerts
|

Condition‐dependent adenosine monophosphate decomposition pathways in striated adductor muscle from Japanese scallop (Patinopecten yessoensis)

Abstract: The purpose of this study was to confirm inosine monophosphate (IMP) generation and to clarify the decomposition pathway of adenosine monophosphate (AMP) by investigating the properties of AMP, IMP, and adenosine (AdR) decomposition enzymes in Japanese scallop (Patinopecten yessoensis). The results showed that IMP accumulated due to AMP decomposition via endogenous enzymes in scallops stored at both 4 °C and 20 °C. The AMP decomposition rate was highest in the supernatant of homogenized scallop adductor muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…AMP was converted to inosine (HxR) and then to hypoxanthine (Hx) during cold storage while the production of HxR and Hx correlates with a loss of freshness in some fish species (Ocaño‐Higuera et al., 2011). As it was reported that there are two AMP decomposition pathways in scallop striated muscle, the conversion of AMP to HxR via adenosine (AdR) or IMP and the AdR pathway is faster (Wei et al., 2020b). Once AdR was produced, it will be immediately decomposed to HxR and Hx so that the existence of AdR can hardly be detected.…”
Section: Resultsmentioning
confidence: 99%
“…AMP was converted to inosine (HxR) and then to hypoxanthine (Hx) during cold storage while the production of HxR and Hx correlates with a loss of freshness in some fish species (Ocaño‐Higuera et al., 2011). As it was reported that there are two AMP decomposition pathways in scallop striated muscle, the conversion of AMP to HxR via adenosine (AdR) or IMP and the AdR pathway is faster (Wei et al., 2020b). Once AdR was produced, it will be immediately decomposed to HxR and Hx so that the existence of AdR can hardly be detected.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonication usually requires more sonication cycles, and it can cause a substantial increase in local temperature of the sample media. Hydrolysis of ATP, ADP, and AMP due to temperature increase was noted in several studies [30][31][32]. Recently, global molecular profiling was used for investigation of the effect of heating on small molecules such as triphosphate nucleotides (ATP, UTP, and GTP).…”
Section: Analysis Of G Fossarum Samples 321 Influence Of Homogenimentioning
confidence: 99%
“…During 0−12 h cold storage, mitochondria still produce ATP, the level of ATP had no significant change. During 12-48 h, mitochondrial activity was greatly reduce, hydrolysis of ATP could produce large amounts of IMP and AdR, and although IMP could not be decomposed in scallop, and no large amount of HxR and Hx were gener- (Wei et al, 2020), resulting in rapid increase of K value. ArP, as the phosphagen scallop adductor muscle, is converted into ATP for rapid supplementation and consumption during the severe exercise of scallops (Grieshaber, 1978).…”
Section: Atp and Its Related Compoundsmentioning
confidence: 99%